(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article discusses the problems in the field of independent education, their solutions and prospects, including the formation of skills and abilities of students by improving the quality of independent education, the organization of teaching in independent education on the basis of combining labor with production, the essence, factors, conditions of independent education. the organizational method, form, and means of this activity, pedagogical technologies, etc.